What Counts As 'Safe?': Exposure To Trauma And Violence Among Asylum Seekers From The Northern Triangle - Cuneo, C Nicholas; Huselton, Kara E; Praschan, Nathan C; Saadi, Altaf; Gartland, Matthew G (Health affairs (Millwood, Va.), 2021)
abstract In 2019 the United States signed Asylum Cooperative Agreements with the Northern Triangle countries of El Salvador, Guatemala, and Honduras, in Central America. In November 2019 the Trump administration announced that these agreements would be used to permit the expedited removal of asylum seekers from the US, claiming that these countries provided comprehensive legal procedures for adjudicating asylum claims and protection against further persecution. To assess the presence of dangerous conditions in the three countries, we examined forensic medical evaluations of asylum seekers from the Northern Triangle who are in the US and who presented to an academic medical center asylum clinic in Boston, Massachusetts, from 2017 to 2020. Northern Triangle asylum seekers reported high rates of exposure to trauma and violence, including gender-based violence and violence perpetrated by gangs, and they also exhibited a high prevalence of trauma-related psychiatric disorders. Asylum seekers also reported state actors in Northern Triangle countries as perpetrators of violence and described denial of protection from the state when it was solicited. These findings cast doubt on key tenets underpinning the legal basis for the Asylum Cooperative Agreements. The agreements should be formally terminated and investigations undertaken to determine the impact on people who were subject to removal from the US during preliminary implementation.